Utilisation Efficiency of Construction Land in China's Coastal Cities Based on Debt Level. (17th April 2020) - Wang, Hui; Qiao, Lu; Tian, Chuang; Lin, Qiaoqiao
Abstract : Optimising the allocation of population, land, and capital production resources is crucial for promoting an efficient urbanisation and solving the urban land financial problem. This study uses a panel threshold model to identify the response boundary of urban construction land use efficiency to government debt level for 51 postfinancial crisis Chinese coastal cities. The results indicate that the threshold of economic development level and provincial gross domestic product (per capita gross domestic product: pgdp) are 2.67 and 5.17, respectively. In cities with relatively backward economic development, an expansion of the government debt scale hinders the improvement of the utilisation efficiency of construction land. Also, the threshold value of the government's accumulated debt level threshold (sd) is 15.83%. When cities fall below the government accumulated debt level threshold (sd < 15.83%), the new debt level has a positive effect on the utilisation efficiency of construction land. When sd > 15.83%, the new debt level impedes the improvement of the utilisation efficiency of construction land. Local governments should reduce their dependence on land finance in cities with high cumulative debt ratios, especially those with negative responses to both thresholds (pgdp and sd thresholds). This study's findings can provide a reference for a sustainable promotion of new urbanisation in both China and in other countries to avoid the risk of land urbanisation.